The Factors Causing Discrimination Against Indonesian Women in the Workplace, Mapping of Problems from 2012 to 2022 - Verdico Arief; Magdalena Depriyani; Asri Hidayati (Green Publisher Indonesia, 2025)
Indonesia, one of the world's most populous nations with a significant female population, continues to face workplace gender discrimination despite legislative frameworks and improving gender equality rankings. Although Indonesia rose to 92nd globally in 2022 (from 99th in 2021), gaps between policy and practice remain, especially regarding women’s participation and advancement in employment. This study fills a critical research gap by systematically mapping factors behind workplace discrimination against Indonesian women. A search across four major databases (ScienceDirect, Emerald Insight, Sage, and Taylor & Francis) for